A Highly Warped Heptagon‐Containing sp2 Carbon Scaffold via Vinylnaphthyl π‐Extension. (30th September 2019) - Farrell, Jeffrey M.; Grande, Vincenzo; Schmidt, David; Würthner, Frank
Abstract: A new strategy is demonstrated for the synthesis of warped, negatively curved, all‐sp 2 ‐carbon π‐scaffolds. Multifold C−C coupling reactions are used to transform a polyaromatic borinic acid into a saddle‐shaped polyaromatic hydrocarbon (2 ) bearing two heptagonal rings. Notably, this Schwarzite substructure is synthesized in only two steps from an unfunctionalized alkene. A highly warped structure of 2 was revealed by X‐ray crystallographic studies and pronounced flexibility of this π‐scaffold was ascertained by experimental and computational studies. Compound 2 exhibits excellent solubility, visible range absorption and fluorescence, and readily undergoes two reversible one‐electron oxidations at mild potentials. Abstract : Kohlenstoffhaltig und kurvenreich : Eine neue Synthesestrategie von heptagonhaltigen, voll‐sp 2 ‐hybridisierten Kohlenstoffgerüsten aus unfunktionalisierten Alkenvorläufern wird beschrieben. So wird ein flexibler, negativ gekrümmter polyaromatischer Kohlenwasserstoff synthetisiert, der eine ausgezeichnete Löslichkeit, Absorption und Fluoreszenz im sichtbaren Bereich und zwei reversible Ein‐Elektronen‐Oxidationen bei geringen Potentialen aufweist.